Sameness and substance renewed - Wiggins, David (Cambridge, United Kingdom : Cambridge University Press, 2001)
In this book, which thoroughly revises and greatly expands his classic work Sameness and Substance (1980), David Wiggins retrieves and refurbishes in the light of twentieth-century logic and logical theory certain conceptions of identity, of substance and of persistence through change that philosophy inherits from its past. In this new version, he vindicates the absoluteness, necessity, determinateness and all or nothing character of identity against rival conceptions. He defends a form of essentialism that he calls individuative essentialism, and then a form of realism that he calls conceptualist realism. In a final chapter he advocates a human being-based conception of the identity and individuation of persons, arguing that any satisfactory account of personal memory must make reference to the life of the rememberer himself. This important book will appeal to a wide range of readers in metaphysics, philosophical logic, and analytic philosophy.
Machine derived contents note: 1. The absoluteness of sameness --2. Outline of a theory of individuation --3. Sortal concepts: their characteristic activity or function or purpose --4. Essentialism and conceptualism --5. Conceptualism and realism --6. Vagueness, determinacy and identity: a conceptualist proposal --7. Personal identity.
Rev. edition of Sameness and substance. Oxford: Blackwell, 1980. Includes bibliographical references and index
Keywords: Identity; Individuation (Philosophy); Essence (Philosophy); Conceptualism; Substance (Philosophy)